Implementasi SIPD dalam Meningkatkan Akuntabilitas Pemerintah Kabupaten Pasuruan - Supeno, Doni Mauludi; Sunariyanto, Sunariyanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the implementation of the Regional Government Information System (SIPD) policy in enhancing the accountability of the Pasuruan Regency Government. SIPD is a digital instrument designed to integrate planning, budgeting, and reporting processes to promote transparent and accountable governance. This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The analysis is based on Edward III’s policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure, and is complemented by Grindle’s perspective on policy content and context. The findings indicate that the implementation of SIPD in Pasuruan Regency has been carried out but has not yet been fully optimized in improving overall accountability. The main challenges lie in ineffective communication, limited human resources and technological infrastructure, and suboptimal coordination among local government agencies. Nevertheless, SIPD has contributed to enhancing transparency and the traceability of administrative processes. This study concludes that the success of SIPD implementation is strongly influenced by organizational readiness and the quality of supporting resources. Therefore, strengthening human resource capacity, improving technological infrastructure, and optimizing inter-agency coordination are necessary to enhance the effectiveness of SIPD in supporting government accountability. Practically, this study recommends that the Pasuruan Regency Government accelerate the strengthening of human resource capacity through continuous technical training and the provision of adequate server infrastructure.